The immunosuppressive drug cyclosporin A has an immunostimulatory function in CD8+ T cells - Wißfeld, Jannis; Hering, Marvin; Bosch, Nora ten; Cui, Guoliang (European journal of immunology, 2024)
Cyclosporin A is a well-established immunosuppressive drug used to treat or prevent graft-versus-host disease, the rejection of organ transplants, autoimmune disorders, and leukemia. It exerts its immunosuppressive effects by inhibiting calcineurin-mediated dephosphorylation of the nuclear factor of activated T cells (NFAT), thus preventing its nuclear entry and suppressing T cell activation. Here we report an unexpected immunostimulatory effect of cyclosporin A in activating the mammalian target of rapamycin complex 1 (mTORC1), a crucial metabolic hub required for T cell activation. Through screening a panel of tool compounds known to regulate mTORC1 activation, we found that cyclosporin A activated mTORC1 in CD8+ T cells in a 3-phosphoinositide-dependent protein kinase 1 (PDK1) and protein kinase B (PKB/AKT)-dependent manner. Mechanistically, cyclosporin A inhibited the calcineurin-mediated AKT dephosphorylation, thereby stabilizing mTORC1 signaling. Cyclosporin A synergized with mTORC1 pathway inhibitors, leading to potent suppression of proliferation and cytokine production in CD8+ T cells and an increase in the killing of acute T cell leukemia cells. Consequently, relying solely on CsA is insufficient to achieve optimal therapeutic outcomes. It is necessary to simultaneously target both the calcineurin-NFAT pathway and the mTORC1 pathway to maximize therapeutic efficacy.
Das Pluszeichen im Titel ist hochgestellt
Online veröffentlicht: 22. April 2024
Gesehen am 19.09.2024